2015
DOI: 10.1016/j.neulet.2015.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of memory consolidation by the histone deacetylase inhibitor sodium butyrate in aged rats

Abstract: Here we show that a systemic injection of the histone deacetylase inhibitor (HDACi) sodium butyrate (NaB) immediately after training in a step-down inhibitory avoidance task produced an enhancement of memory consolidation that persisted across consecutive retention tests during 14 days in aged rats, while it did not significantly affect memory in young adults. Control aged and young adult rats showed comparable basal levels of memory retention. Our results suggest that HDACis can display memory-enhancing effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Rats were implanted under anesthesia with isoflurane (vaporized in 100% oxygen, at a dose of 5% for induction and 2% for maintenance, in a fraction of 0.5 l/min) with bilateral 8-mm, 23-gauge guide cannulae aimed 1.0 mm above the dorsal hippocampus, as described previously [6,7]. Coordinates (anteroposterior, -4.3 mm from bregma; mediolateral, ±3.0 mm from bregma; ventral, -2.0 mm from skull surface) were obtained from the atlas of Paxinos and Watson [38].…”
Section: Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…Rats were implanted under anesthesia with isoflurane (vaporized in 100% oxygen, at a dose of 5% for induction and 2% for maintenance, in a fraction of 0.5 l/min) with bilateral 8-mm, 23-gauge guide cannulae aimed 1.0 mm above the dorsal hippocampus, as described previously [6,7]. Coordinates (anteroposterior, -4.3 mm from bregma; mediolateral, ±3.0 mm from bregma; ventral, -2.0 mm from skull surface) were obtained from the atlas of Paxinos and Watson [38].…”
Section: Surgerymentioning
confidence: 99%
“…1. The general procedures for IA behavioral training and retention tests were described in previous reports [6,7] On training trials, the rats were placed on the platform and their latency to step down on the grid with all four paws was measured with a digital chronometer. Immediately after stepping down on the grid, the rats were given a 0.4-mA, 3.0-s footshock and then removed from the apparatus immediately afterward.…”
Section: Inhibitory Avoidance (Ia)mentioning
confidence: 99%
See 2 more Smart Citations
“…NaB and other inhibitors including trichostatin A (TSA), suberoylanilide hydroxamic acid (SAHA), and valproic acid have been shown to enhance LTP and the formation and extinction of memory for fear-motivated tasks (Blank et al 2014;Bredy and Barad 2008;Lattal et al 2007;Levenson et al 2004;Stafford et al 2012;Vecsey et al 2007). We have previously shown that infusions of either NaB or TSA into the dorsal hippocampus given immediately or 3 h after training resulted in a long-lasting enhancement of IA memory (Blank et al 2014), and systemic administration of NaB enhanced memory in aged rats (Blank et al 2015;Reolon et al 2011).…”
Section: Introductionmentioning
confidence: 99%